Physician Perceptions about the Barriers to Prompt Diagnosis of Mild Cognitive Impairment and Alzheimer's Disease. (21st May 2019) - Judge, Davneet; Roberts, Jenna; Khandker, Rezaul; Ambegaonkar, Baishali; Black, Christopher M.
Abstract : Prior studies have identified numerous barriers to the prompt diagnosis of patients with suspected Alzheimer's disease (AD). The aim of the study was to evaluate physician's perceptions of the importance of previously identified barriers to diagnosis, but with a specific focus on the presentation of mild cognitive impairment (MCI), which may be indicative of neurodegenerative disorders such as AD. A second aim was to evaluate how the perspective of primary care physicians (PCPs) may differ from that of specialists. A cross-sectional online survey of PCPs and specialists who routinely manage patients with complaints of age-related cognitive impairment was conducted. Participants were asked to identify barriers to prompt diagnosis from prespecified lists of known diagnostic challenges categorized into 4 domains: patient-related, physician-related, setting-related, and those relating to the clinical profile of AD. Physicians report a range of barriers when attempting to diagnose MCI and AD. Major themes included patients seeing cognitive decline as a normal part of aging and not disclosing symptoms, long waiting lists, and a lack of treatment options and definitive biomarker tests. Generally, PCPs and specialists showed broad agreement; however, PCPs were more likely to identify burdens on the healthcare system, such as long waiting lists and inadequate time to evaluate patients. Substantial barriers continue to hinder early diagnosis of MCI and AD. There are numerous areas where improvements might be made but the implementation of potential interventions will likely be associated with financial strain for many healthcare systems.